2015
DOI: 10.1038/modpathol.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

CD5-positive follicular lymphoma: clinicopathologic correlations and outcome in 88 cases

Abstract: Follicular lymphoma is a low-grade B-cell lymphoma of germinal center B-cell origin that typically lacks CD5 expression. We describe the clinicopathologic features of 88 cases of CD5+ follicular lymphoma (53 men, 35 women; median age, 60 years; range, 31-86). Follicular lymphoma was diagnosed initially in lymph nodes in 66 and extranodal sites in 22 patients. Eighty-one patients had lymphadenopathy, 66 had more than one involved site, 46 had bone marrow involvement, and 7 had splenomegaly. Staging information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…[15,16] It has also been found to be expressed in follow up biopsies of FL which initially did not express.…”
Section: Resultsmentioning
confidence: 99%
“…[15,16] It has also been found to be expressed in follow up biopsies of FL which initially did not express.…”
Section: Resultsmentioning
confidence: 99%
“…More interestingly, our case showed CD5 to be strongly and extensively positive in tumor cells, with aberrant co‐expression of CD5, CD10, and IFR4/MUM1. CD5‐positive FL and DLBCL in adults were correlated with a more aggressive clinical course as well as worse prognosis …”
Section: Discussionmentioning
confidence: 99%
“…IRTA-1 is specific for marginal zone B-cell lymphoma and is useful for diagnosis. 13 Li Y et al 14 reported 88 patients with CD5-positive follicular lymphoma. For MZL, CD5-positive patients often exhibit dissemination, bone marrow involvement, and/or leukemic state.…”
Section: Other Cd5-positive Lymphomasmentioning
confidence: 99%